COMPREHENSIVE STUDY OF BIOETHANOL FROM CASSAVA AS A SUBTITUTE FOR FUEL OIL - Tirangga Ansori; Degdo Suprayitno; Dewa Oka Suprawata; Ivonne Fitria Mariay; Usman Tahir (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Fuel oil (BBM) consumption in Indonesia has increased from year to year, but the availability of fuel oil will gradually become scarce. Bioethanol can be used as a substitute for fuel oil (BBM) depending on its purity level. Bioethanol is a liquid resulting from the fermentation process of sugar from carbohydrates which has good prospects as a liquid fuel with raw materials that are renewable, environmentally friendly and very profitable economically. Bioethanol can be used as a gasoline mixture for vehicle fuel and can be used as cooking fuel in households. The use of bioethanol can reduce CO gas emissions significantly. Bioethanol can be used directly as fuel oil or mixed into premium as an additive in a certain ratio (Gasohol or Gasoline alcohol). If mixed into gasoline, bioethanol can increase the octane number significantly. Bioethanol is known as an environmentally friendly fuel, because it is free from pollutant emissions. Bioethanol can be made from plant raw materials that contain starch such as cassava, sweet potato, corn, sago and molasses. One of the materials that can be used to make fuel from ethanol is the cassava plant. Cassava is a tuber that contains carbohydrates that come from the roots of the cassava plant. Cassava is very easy to plant and maintenance is not difficult. Cassava is usually used as a substitute for rice, but can also be used as an alternative to fuel oil. This research is qualitative research with a descriptive approach. Researchers use research data in the form of secondary data obtained from a number of credible sources such as scientific articles, books and a number of other sources that are credible and commonly used in research. These data were analyzed using analytical tools with stages of data collection, data selection, data reduction and drawing conclusions. Keywords: Fuel Oil, Bioethanol, Cassava